Analysis on the energy efficiency, thermal performance and infection intervention characteristics of interactive cascade ventilation (ICV). (1st June 2023) - Kong, Xiangfei; Wang, Zhaoying; Fan, Man; Li, Han
Abstract: Floor radiation (FR) is one of the widely used heating modes in winter. However, the widespread and high outbreak of Corona Virus Disease 2019 (COVID-19) has made the disadvantage of floor radiation that lacks fresh air and air movement exposed as a deficiency. To seek a heating mode that can realize a comfortable and healthy indoor environment with low cost, the interactive cascade ventilation (ICV) coupling with multiple low-grade sources was proposed in this study. Energy efficiency, thermal comfort and air quality were investigated by comparing with FR and floor radiation with mixing ventilation (FRMV). The results showed that by elevating the same indoor temperature, ICV can reduce indoor heat transfer by 28.41% and 30.94% than FR and FRMV, respectively. And ICV also presented the highest system COP by introducing multiple low-grade sources. In terms of thermal comfort, the indoor environment served by ICV was closer to thermal neutrality, and the subjective thermal comfort can also be enhanced by 10% and 8% relative to FR and FRMV. The CO2 test results indicated that by introducing the ICV, indoor air quality can be improved by 36.68% and 61.45% over FR and FRMV with the contaminant removal rate significantly accelerated. During the pandemic, ICV can reduce the COVID-19 infection rate by 9.6% and 55.5% within 8 h and 30 min compared with FRMV. The conclusions obtained in this paper can provide new ideas for designing air conditioning systems in the epidemic and the context of carbon reduction. Highlights: The performance of interactive cascade ventilation (ICV) was investigated. ICV reduces the power consumption by 33.95%. ICV can enhance the indoor comfort by 8%–10%. ICV improves indoor air quality by 36.68%–61.45%. ICV reduces the infection rate by 55.5% within 30min.